5‐week block periodization increases aerobic power in elite cross‐country skiers. Issue 2 (3rd February 2015) - Rønnestad, B. R.; Hansen, J.; Thyli, V.; Bakken, T. A.; Sandbakk, Ø.
Abstract : The purpose of this study was to compare the effect of two different methods of organizing endurance training in elite cross‐country skiers approaching the competition period. During the 5‐week intervention period, one group performed block periodization (BP; n = 10) with 5 and 3 high‐intensity sessions (HIT) during the first and third training week. One HIT was performed during the remaining weeks in BP, while the group performing traditional training organization (TRAD, n = 9) performed two weekly HIT except during the third week where they performed three HIT. HIT were interspersed with low‐intensity training (LIT) and both groups performed similar total amount of both HIT and LIT during the intervention. BP achieved a larger relative increase in peak power output and power output at a blood lactate concentration of 4 mmol/L than TRAD (4 ± 4 vs −3 ± 6% and 11 ± 10 vs 2 ± 4%, respectively, both P < 0.01). BP also increased maximal oxygen uptake by 2 ± 2% ( P < 0.05), while no changes occurred in TRAD. The effect sizes of the relative improvement in these measurements revealed moderate effects of BP vs TRAD training. The present study suggests that block periodization of endurance training have superior effects on several endurance and performance indices compared with traditional organization.